Characteristics of Green Tea Kombucha with Added Jasmine Flowers - Rahma, S.A.; Novelina, Novelina; Ismed (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
The objective of this study is to assess the impact of jasmine flower enrichment on the quality attributes of green tea kombucha.The research design was the treatment of adding jasmine flowers with concentrations A (0%), B (0.4%), C (0.8%), D (1.2%), and E (1.6%), repeated three times. The data obtained were analyzed statistically using analysis of variance (ANOVA). If significantly different, the data analysis was continued with the DNMRT (Duncan's New Multiple Range Test) at a significance level of 5%. The results showed that the addition of jasmine flowers had a significant effect on the degree of acidity (pH), total acetic acid, and sugar content. However, the addition of jasmine flowers to green tea kombucha did not significantly affect the results of the analysis of ethanol content, antioxidant activity, and essential oil compounds. The best treatment was the addition of 0.8% jasmine flowers, with a pH value of 3.31, acetic acid content of 2.18%, ethanol content of 0.36%, total sugar content of 2.77%, antioxidant activity of 46.14% in 1000 ppm, total microbes of 5.2 x 106 CFU/ml and essential oil compounds of 1.12%, and the sensory attribute value of kombucha was like. Contribution to Sustainable Development Goals (SDGs)SDG 3: Good Health and Well-beingSDG 12: Responsible Consumption and ProductionSDG 9: Industry, Innovation and Infrastructure